Value Stream Mapping and Fishbone Diagram to Analyze Waste Analysis in Lapis Tugu Kediri - Naufal, Enrikko Ahmad; Wurjaningrum, Febriana (Southeast Asian Business Review, 2025)
The Lapis Tugu Kediri is a SME facing several waste-related issues that reduce its productivity. Using a qualitative approach, the research consists of two phases. First, a value stream mapping of the production flow is created and analyzed using value stream mapping tools. Next, a fishbone diagram is developed to identify the sources of waste before proposing improvements. The research revealed several types of waste in the production process, with the most significant being overprocessing and unnecessary motion. The value stream mapping highlighted specific sections where waste occurs, while the fishbone diagram identified root causes such as the absence of a timer in the baking section and an unqualified production table. Based on these findings, targeted improvements were proposed to eliminate waste and optimize the production flow. The research has been validated using data triangulation at a single SME, providing deep insight and information. However, further research on other SMEs or using a different methodology within the same SME is encouraged. Value stream mapping and fishbone diagram is a useful combination in terms of analyzing waste in the SME scope. The validation of analyzing waste through value stream mapping and fishbone diagram is well-documented and original.